2002
DOI: 10.3168/jds.s0022-0302(02)74397-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heat Stress on Nonreturn Rate in Holsteins: Fixed-Model Analyses

Abstract: The objective of this study was to examine the relationship between reproductive traits and heat stress. Nonreturn rate at 45 d (NR45) was analyzed in a fixed-effect model that included the temperature-humidity index (THI) from a nearby weather station as a measurement of heat stress. Data consisted of 150,200 first inseminations at first and later parities of 110,860 Holstein cows from 550 herds in Georgia, Tennessee, and Florida with weather information from 16 weather stations. THI on the day of the insemin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
1
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(83 citation statements)
references
References 13 publications
4
74
1
4
Order By: Relevance
“…Most selection relevant to climate adaptation is undertaken in developed countries with commercial breeds, most of which are of temperate origin. Considerable genetic variance caused by heat stress was related to high daily THI in Jersey and Holstein Friesian dairy cattle (Ravagnolo and Misztal, 2002;Hayes et al, 2009). Therefore, selection for heat tolerance in highoutput breeds based on rectal temperature measurements and inclusion of a THI in genetic evaluation models is promising.…”
Section: Analysis Of Breed Data Within Dad-ismentioning
confidence: 99%
“…Most selection relevant to climate adaptation is undertaken in developed countries with commercial breeds, most of which are of temperate origin. Considerable genetic variance caused by heat stress was related to high daily THI in Jersey and Holstein Friesian dairy cattle (Ravagnolo and Misztal, 2002;Hayes et al, 2009). Therefore, selection for heat tolerance in highoutput breeds based on rectal temperature measurements and inclusion of a THI in genetic evaluation models is promising.…”
Section: Analysis Of Breed Data Within Dad-ismentioning
confidence: 99%
“…Hansen (2007) postulated that identification of the genes that are responsible for heat tolerance in cattle could diminish the risk of embryonic mortality, which is currently the leading cause of fertility problems in high yielding dairy cows (Diskin and Morris, 2008). Data comparing non-return rates at day 45 after artificial insemination (AI) in Holstein/Friesian cows in different states of the United States showed that resistance to heat stress varies possibly because of a genetic variability in heat tolerance within the breed (Ravagnolo and Misztal, 2002). Unravelling the underlying mechanisms by which heat stress impairs male fertility may help to alleviate the effects on sperm quality and subsequent embryo development.…”
Section: Effects Of Hyperthermia On Dna Integrity and Embryonic Develmentioning
confidence: 99%
“…Many studies from so called 'hot weather areas' in the world found a decline in milk production and a depression of reproductive performance in dairy cows due to heat stress (e.g. Ravagnolo & Misztal 2002, Bohmanova et al 2007.…”
Section: Introductionmentioning
confidence: 99%